An adenoviral vector encoded with the GPx-1 gene attenuates memory impairments induced by β-amyloid (1-42) in GPx-1 KO mice via activation of M1 mAChR-mediated signalling. (2nd January 2021) - Shin, Eun-Joo; Lee, Sung Hoon; Sharma, Naveen; Nguyen, Bao Trong; Chung, Yoon Hee; Kang, Sang Won; Nah, Seung-Yeol; Lee, Yu Jeung; Nabeshima, Toshitaka; Jeong, Ji Hoon; Kim, Hyoung-Chun
Abstract: In the present study, we examined whether glutathione peroxidase-1 (GPx-1), a major H2 O2 scavenger in the brain, affects memory deficits induced by Aβ (1-42) in mice. Treatment with 400 pmol/5 μl Aβ (1-42) (i.c.v.) resulted in a reduction of GPx-1 expression in wild-type (WT) mice. An Aβ (1-42)-induced reduction in acetylcholine (ACh) level was observed in the hippocampus. Treatment with Aβ (1-42) consistently resulted in reduced expression and activity of choline acetyltransferase (ChAT) and in an increase in expression and activity of acetylcholinesterase (AChE). Upon examining each of the muscarinic acetylcholine receptors (mAChRs) and nicotinic AChRs, we noted that Aβ (1-42) treatment selectively reduced the levels of M1 mAChR. In addition, Aβ (1-42) induced a significant reduction in phospho-cAMP response element-binding protein (p-CREB) and brain-derived neurotrophic factor (BDNF) expression. The cholinergic impairments induced by Aβ (1-42) were more pronounced in GPx-1 knockout mice than in WT mice. Importantly, an adenoviral vector encoded with the GPx-1 gene (Ad-GPx-1) significantly rescued Aβ (1-42)-induced cholinergic impairments in GPx-1 knockout mice. In addition, M1 mAChR antagonist dicyclomine significantly counteracted Ad-GPx-1-mediated increases in p-CREB and BDNF expression, as well as memory-enhancing effects in GPx-1 knockout mice, thus indicating that M1 mAChR might be a critical mediator for the rescue effects of Ad-GPx-1. Combined, our results suggest that GPx-1 gene protected against Aβ (1-42)-induced memory impairments via activation of M1 mAChR-dependent CREB/BDNF signalling. Graphical abstract: UF0001